2021
DOI: 10.1177/02676591211034314
|View full text |Cite
|
Sign up to set email alerts
|

Use of bivalirudin for anticoagulation in pediatric extracorporeal membrane oxygenation (ECMO)

Abstract: This study describes the use of bivalirudin in children on extracorporeal membrane oxygenation (ECMO). Pediatric patients receiving bivalirudin were compared to patients receiving heparin as the anticoagulant on ECMO. Data was collected for children under 18 years of age supported by ECMO from January 2016 to December 2019. Data collected included demographics, diagnosis, ECMO indication, type, and duration, indication for bivalirudin use, dose range, activated partial thromboplastin time (aPTT) levels, minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 20 publications
0
41
0
2
Order By: Relevance
“…No articles on the subject were found in CNKI. After screening and evaluation, ten articles [12][13][14][15][16][17][18][19][20][21] were finally included for qualitative synthesis, and nine articles [12][13][14][15][16][17][19][20][21] were included in the meta-analysis because one reference [18] met the inclusion criteria but the data of outcome presented could not be pooled in a meta-analysis. The literature retrieval and screening processes are shown in Fig.…”
Section: Literature Retrieval Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…No articles on the subject were found in CNKI. After screening and evaluation, ten articles [12][13][14][15][16][17][18][19][20][21] were finally included for qualitative synthesis, and nine articles [12][13][14][15][16][17][19][20][21] were included in the meta-analysis because one reference [18] met the inclusion criteria but the data of outcome presented could not be pooled in a meta-analysis. The literature retrieval and screening processes are shown in Fig.…”
Section: Literature Retrieval Results and Study Characteristicsmentioning
confidence: 99%
“…All data generated or analyzed during this study are included in this published article (shown in Reference [9][10][11][12][13][14][15][16][17][18]).…”
Section: Abbreviationsmentioning
confidence: 99%
“…In total 17 studies published from years 2011 to 2022 and one unpublished study were included in this metaanalysis [9][10][11][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. All studies had a retrospective study design and only one study was multi-center.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There is also no consensus on whether a loading dose should be used or not. In studies comparing the 2 strategies, the difference in time to achieving therapeutic levels was only 4 h ( 27 ). Further studies are required to determine the safety and risk for bleeding with bolus dosing.…”
Section: Direct Thrombin Inhibitors: Bivalirudinmentioning
confidence: 99%